2014
DOI: 10.3329/bjpp.v30i1.20791
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of obesity and the novel adipocytokines, leptin and adiponectin with insulin resistance in type 2 diabetes

Abstract: Back ground: Type 2 Diabetes mellitus is state of uncompensated insulin resistance. But what actually predisposes to it, is still a controversy. Obesity is often marked as a precondition for such insulin resistance. But the degree of association and mode of pathogenesis are grossly debated. Methods:Here we explored the correlation of physical parameters for obesity like BMI (Body Mass Index), abdominal circumference, waist-hip ratio and the adipocytokines like leptin and adiponectin with the degree of insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…21 Meanwhile from Buyukbese study, we had leptin levels to be 40.22±17.77 ng/ml in diabetes compared to 50.12±15.55 ng/ml in the control though the later cases were all obese which corresponds to the study of that states the association of a higher leptin level with obesity. [22][23][24] This is in contrast to this study as the leptin levels in the diabetes were not significantly different from the control which corroborates the report from Haffner which stated a non significant differences in the concentratrion of leptin in diabetes and non diabetes. 25 This study agrees with the report of Abu-Ssayed where low levels of leptin may be attributed to lean diabetics which might be as a result of the fat distribution within the subjects since they are all on normal weight.…”
Section: Discussionsupporting
confidence: 83%
“…21 Meanwhile from Buyukbese study, we had leptin levels to be 40.22±17.77 ng/ml in diabetes compared to 50.12±15.55 ng/ml in the control though the later cases were all obese which corresponds to the study of that states the association of a higher leptin level with obesity. [22][23][24] This is in contrast to this study as the leptin levels in the diabetes were not significantly different from the control which corroborates the report from Haffner which stated a non significant differences in the concentratrion of leptin in diabetes and non diabetes. 25 This study agrees with the report of Abu-Ssayed where low levels of leptin may be attributed to lean diabetics which might be as a result of the fat distribution within the subjects since they are all on normal weight.…”
Section: Discussionsupporting
confidence: 83%
“…Study concluded that, obesity mainly of central or abdominal type might be responsible for the insulin resistance in type 2 diabetes mellitus whereas leptin, a potential marker for obesity was probably not involved. This perhaps points towards the multifactorial causation of insulin resistance in type 2 diabetes mellitus [8].…”
Section: Discussionmentioning
confidence: 95%
“…which are released by the adipose tissue, thus it is suggested that such altered level of adipokines are involved in the pathogenesis of obesity associated diabetes. Leptin level increases in obesity and its correlation with body mass index (BMI) and glucose levels has already been reported in different populations [8][9][10][11]. As we already had reported blood levels of adiponectin in a small population from Faisalabad, Pakistan [12] there is no such data for leptin levels for this population.…”
Section: Introductionmentioning
confidence: 92%
“…[34] Contrary to previous studies, Martin et al found a direct positive association between obesity and serum leptin, hyperinsulinemia, and IR but not strong relation to other components of metabolic syndrome [35] on other hand, previously concluded that serum leptin, through obesity marker, does not significantly end towards the multifactor causation of interactions between adipocytokines are proposed to be involved in the defect in IR, and any single molecule alone including leptin may have not significant associations with the level of IR. [36] Increased leptin levels in obese, diabetic patients may indicate leptin resistance; and since leptin is a strong regulator of insulin sensitivity/glucose homeostasis, it is possible that when leptin resistance develops it may worsen IR.…”
Section: Discussionmentioning
confidence: 99%